The Apple way - Cruikshank, Jeffrey L., Lusiana Rumintang (Esensi, 2008)
Apple's stock has increased in value an unprecedented 250 percent in the past year, and a two-for-one split was announced in February 2005. More than 10 million iPods have sold, putting Apple at the forefront of the digital music revolution. This book is filled with real-world examples of Apple's phenomenally successful management principles, and is written by the bestselling author of several Harvard Business School Press titles.